Legal Certainty of P-IRT Through the BPOM Post Market in View of Law Number 8 of 1999 Concerning Consumer Protection - Yustino Aribawa, Muhammad; Octarina, Nynda Fatmawati (State of Islamic Institute Langsa, 2023)
The current circulation of processed products from home industries makes product standardization certification important as an effort to protect the public. This study aims to explain the legal certainty of P-IRT and post market BPOM as an effort to protect consumers. The method used in this research is the normative juridical method which is carried out with a statutory approach and with an analytical approach. The specification used is conceptual descriptive. The data that will be used is secondary data including legislation and literature relevant to P-IRT and Post Market BPOM. From the research conducted, the results showed that the implementation of P-IRT based on BPOM Regulation Number 22 of 2018 can be a protection for the public from harmful products. As a responsibility for the supervision of products that have given P-IRT certificates, the implementation of post market supervision by BPOM on the basis of implementation of BPOM Regulation Number 9 of 2020 as a form of protecting consumer rights as stipulated in Law Number 8 of 1999 concerning Consumer Protection. In their application, both show clear legal certainty for consumers.